Field testing to predict performance in rugby union players - Green, B.; Blake, C.; Caulfield, B. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to identify the relationships between various field tests for leg power, sprinting speed and agility in a group of rugby union players. A group of 26 semi professional rugby union players each completed a test protocol consisting of a unilateral horizontal triple jump, 10 and 30M linear speed sprint tests, a change of direction test and a reactive agility speed test. Simple correlation analysis revealed multiple strong relationships between measured variables, most notably between linear speed and reactive agility speed (r=0.72-0.83). Multiple regression analysis indicated that linear speed and change of direction speed could predict 81% of the variance in reactive agility speed.